Analysis of the Subjective Well-Being of the Player of Paddle - Villena-Serrano, Manuel; Castro-López, Rosario; Zagalaz-Sánchez, María Luisa; Cachón-Zagalaz, Javier (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
Due to the importance of paddle in Spain, the purpose of this study was to deepen the analysis of the subjective welfare state of the player of this sport. For this, three factors of intimate relationship with happiness were analyzed, such as, happiness itself, satisfaction with life and mood. The study involved 118 subjects, of average age 31.86 years (SD = ± 8.959). The instruments used to evaluate these constructs were the Factor Scale to measure Happiness, Satisfaction With Life Scale (SWLS) and the Profile of Mood States (POMS). The analysis has revealed the correlation between the three factors. The results indicate that as the practice time increases the paddle players obtain more favorable scores for the different dimensions of the state of mind (POMS). Regarding the results obtained, it is considered that there is a positive relationship between the practice of paddle sports and the subjective well-being of the person.